Effects of morning and nocturnal soccer matches on levels of some trace elements in young trained males - Algul, Sermin; Bengu, Aydin Sukru; Baltaci, Saltuk Bugra; Ozcelik, Oguz (Cellular and Molecular Biology, 2019)
The aim of this study was to comparatively evaluate effect of morning and nocturnal soccer matches induced metabolic stress on plasma levels of iron (Fe), copper (Cu) and zinc (Zn). Twenty male footballers performed two soccer matches in morning and at night on different days. Blood samples were taken before and after match. The levels of Fe, Zn and Cu were measured through an atomic absorption spectrophotometry. Metabolic stress was evaluated by altered malondialdehyde (MDA) levels that measured using High Performance Liquid Chromatography. In morning and at nocturnal soccer matches, levels of MDA (36% and 27%), Fe (37.4% and 38.9%) and Cu (34.8% and 26.8%) were all increased in all subjects, respectively. However, Zn level decreased -4.5 % in morning (n=10 subjects) and -9.4% at nocturnal (n=12 subjects) soccer matches. In addition, Cu/Zn ratio increased significantly 46.6% in morning and 36.6% at nocturnal soccer matches. Soccer match has significant effects on levels of MDA, Fe and Cu but not Zn levels. The results of this study showed that morning soccer match significantly alters levels of MDA and Cu and Cu/Zn ratio compared to nocturnal soccer match.